2020
DOI: 10.3390/biology9070150
|View full text |Cite
|
Sign up to set email alerts
|

Heterometrus spinifer: An Untapped Source of Anti-Tumor Molecules

Abstract: Despite intensive research, cancer incidence and mortality continue to rise. Consequently, the necessity to develop effective anti-cancer therapy is apparent. We have recently shown that the gut bacteria of animals living in polluted environments, such as crocodiles, are a potential source of novel anti-tumor molecules. To extend this work to other resilient species, we investigated the anti-tumor effects of gut bacteria of Heterometrus spinifer (a scorpion). Bacteria from the feces and gut were isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Through LC–MS, we also noted that those bacteria produced molecules with previously reported anticancer activity; 3-butylidene-7-hydroxyphthalide, U-0126, and proglumide. However, the LC–MS revealed that the active bacteria also produce molecules with reported antibacterial activities, namely dextromethorphan, citric acid, and 3-Butylidene-7-hydroxyphthalide [ 83 ].…”
Section: The Importance Of the Gut Microbiomementioning
confidence: 99%
“…Through LC–MS, we also noted that those bacteria produced molecules with previously reported anticancer activity; 3-butylidene-7-hydroxyphthalide, U-0126, and proglumide. However, the LC–MS revealed that the active bacteria also produce molecules with reported antibacterial activities, namely dextromethorphan, citric acid, and 3-Butylidene-7-hydroxyphthalide [ 83 ].…”
Section: The Importance Of the Gut Microbiomementioning
confidence: 99%